La planeación y el presupuesto como sistemas simbólicos articulados a los procesos de resistencia campesina: análisis de una organización a partir de los referentes teóricos de Pierre Bourdieu (2015)
In order to expand the framework for understanding the role played by accounting in organizations, an analysis from the conceptual elements of the French theorist Pierre Bourdieu, analyzing the situation of an organization of peasant resistance is proposed, identifying articulation of planning and budgeting with the social process set up by the community, seeking to demonstrate how the discipline operates in a context with qualitatively divergent logics from those prevailing in the organizational environment of private enterprise. From this, the planning and budgeting are understood as a symbolic system where there are logics that allow cognition and communication, in a process in which power relationships overlap.Product of a particular form of relationship, accounting is understood as a knowledge in which reality is recreated and built, by a community. It falls under the framework of specific relationships of power that transcend it and penetrate the social construction, beyond the purely economic and financial frameworks.